Strengthening discipline and responsibility through btq extracurricular at smp negeri 1 candimulyo - Abdunrorma Sama Alee; Dicha Gadis Janata; Zaharah (Amorti: Jurnal Studi Islam Interdisipliner, 2025)
This research aims to find out the implementation of tasmi' and murojaah methods to accelerate hafalan al quran jul 30 on the centri. The research results are as follows.  First, strengthening character education for discipline and responsibility for BTQ extracurricular activities, a. The role of the teacher influences the character of students, b. by holding religious activities at school c. providing motivation and guidance to implement the character of discipline and responsibility. Second, supporting factors include, a. the active role of the school principal, b. active role of teachers, c. active role of parents and family environment, d. Students' awareness, while inhibiting factors include, a. Lack of school infrastructure, b. Family factors. Third, solutions for dealing with inhibiting factors, namely, a. From the institution, there are more suggestions and infrastructure needed for teachers and students to support BTQ extracurricular religious activities, namely by building prayer rooms, providing toilets and ablution places, providing carpets, prayer mats and mukenas and keeping these infrastructure clean. b. Ask parents to always train their children to carry out religious activities such as praying five times a day and also reciting the Koran at home.